Probing orbital order with soft x-rays: the case of the manganites - Wilkins, S; Beale, T; Hatton, P; Purton, J; Bencok, P; Prabhakaran, D; Boothroyd, A (IOP Publishing, 2005)
We have investigated the orbital and magnetic correlations of the manganese sub-lattice in the archetypical half-doped manganite La 0.5Sr 1.5MnO 4 using the enhanced sensitivity of resonant soft x-ray diffraction at the Mn L edges. We have separately measured the energy dependence of the scattered intensity from both the (1/4, 1/4, 0) and (1/4,1/4,1/2) reflections indicative of the long-range correlations of orbital and magnetic order respectively. Measurements of the integrated intensity of the different features in the resonant energy spectrum show the different origins of the orbital correlations and their variation with temperature. The results also give evidence for a strong coupling between the orbital and spin degrees of freedom. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.